Effect of Urease Enzyme on Shear Strength of Clay Shale - Joseph Henri Nainggolan, Maxwel; Rahayu, Wiwik; Lisdiyanti, Puspita (International Journal of Engineering and Technology, 2018)
In recent years, utilization of biotechnology in geotechnical field has rapidly grown. One of the biotechnologies being utilized is urease enzyme, a stabilization material by bio-cementation method studied in this research.Â Urease enzyme is manually mixed with additional 10% of clay soil to clay shale. The objective of mixing it is to increase the bearing capacity of the clay shale. Consolidated undrained triaxial test was performed for testing the soil strength performance for samples that had undergone curing for 2, 4, and 6 weeks. The results indicated that the sample stiffens, proved by the increase of shear strength from consolidated undrained triaxial test. The shear strength value produced by the variation of the urease enzyme mixture + 10% the clay is higher than that of without the original clay shale.Â Â